2002
DOI: 10.2337/diabetes.51.4.1263
|View full text |Cite
|
Sign up to set email alerts
|

Increased Proinsulin Levels and Decreased Acute Insulin Response Independently Predict the Incidence of Type 2 Diabetes in the Insulin Resistance Atherosclerosis Study

Abstract: Previous studies have indicated that ␤-cell dysfunction predicts the development of diabetes, although it is unknown whether the use of combinations of insulin secretory measures further improves prediction. The Insulin Resistance Atherosclerosis Study is a prospective, multicenter, epidemiological study of the relationship between insulin sensitivity and the risk of diabetes and cardiovascular disease. At baseline, fasting concentrations of insulin, intact proinsulin (PI), and split PI were measured, and acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
75
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 65 publications
(66 reference statements)
11
75
0
Order By: Relevance
“…Interestingly, the HOMA analysis showed that subjects with IFG have more pronounced impairments of beta cell function than subjects with IGT. We also observed increased PI levels in males with IFG as compared to IGT, which may indicate more pronounced impaired beta cell responsiveness in IFG [19]. However, an influence of insulin resistance in this context cannot be ruled out [20].…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, the HOMA analysis showed that subjects with IFG have more pronounced impairments of beta cell function than subjects with IGT. We also observed increased PI levels in males with IFG as compared to IGT, which may indicate more pronounced impaired beta cell responsiveness in IFG [19]. However, an influence of insulin resistance in this context cannot be ruled out [20].…”
Section: Discussionmentioning
confidence: 56%
“…Although the magnitudes of the associations were weaker than those for S i , there were a number of notable ethnic differences, including a stronger association of NCEP-MetS with low AIR and low DI among blacks. This observation is significant in light of the well-documented prospective association between ␤-cell dysfunction and risk of diabetes, an association that is independent of directly measured insulin sensitivity (45,46). The biological mechanism underlying the association between MetS and ␤-cell dysfunction may be related to the fact that a number of MetS components, including elevated abdominal obesity and triglyceride concentration and reduced HDL levels, are strongly correlated with elevated circulating concentrations of free fatty acids (47), chronic elevations of which are known to be associated with lipotoxic damage to the pancreatic ␤-cells (48).…”
Section: Discussionmentioning
confidence: 94%
“…It was recently reported that the proinsulin : insulin ratio and the acute insulin response were independent predictors of type 2 diabetes. Individuals with a combination of a low acute insulin response and a high proinsulin : insulin ratio were at the highest risk of developing type 2 diabetes [39]. Furthermore, in a recent Swedish study proinsulin predicted cardiovascular death and morbidity over a period of 27 years, independently of other major cardiovascular risk factors [40].…”
Section: Discussionmentioning
confidence: 98%